Sex differences in coronary artery bypass grafting-related morbidity and mortality - Nurkkala, Jouko; Kauko, Anni; Palmu, Joonatan; Aittokallio, Jenni; Niiranen, Teemu (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary artery bypass grafting (CABG) is associated with both cardiovascular disease (CVD) and non-CVD traits. In addition, women’s prognosis after coronary events and revascularizations is worse than in men. As the course of CVD in women differs from that of men, we performed a phenome-wide analysis on the sex differences in CABG -related morbidity and mortality. Methods: We performed an untargeted analysis on the sex differences in predictors and outcomes of CABG. We studied a sample of 176,680 FinnGen participants, including 5,950 individuals who underwent CABG (4,988 men and 962 women) and were followed between 1998-2019. Over 1100 different traits were analyzed for both sexes and the results were adjusted with age, smoking status and BMI. Cox proportional hazards models with sex-trait interactions were used to estimate the associations between 1) traits and incident CABG; and 2) CABG and incident traits. Results: In women, CABG was more strongly related to greater increases in risk of diseases such as hypertension, Alzheimer’s, aortic aneurysms, gout, and chronic kidney disease compared to risk increases observed in men (all interaction p-values <0.03). After CABG, men had 2.5-fold (p=3.1E-15) and women 6.3-fold (p=9.4E-08) greater risk of cardiac death compared to same-sex individuals who did not undergo CABG (p for interaction 8.2E-4). Moreover, the risk of death in women remained higher even 12 years after CABG, whereas the long-term risk of death in men was not increased, compared to same-sex individuals who did not undergo CABG. Conclusions: The adverse outcomes after CABG, both quantity and quality, also appear to differ between men and women. In women, CABG is related to greater long-term increases in risk of cardiac death and several other disease states than in men. Consideration should therefore be given to whether women receive adequate long-term post-operative therapy and follow-up as CABG is not associated with equally improved cardiovascular disease prognosis in women than in men.